DISTRIBUSI PENGELUARAN KONSUMSI RUMAH TANGGA PETANI KARET EKS UPP TCSDP DAN PETANI SWADAYA DI DESA BINA BARU KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Leny Surya Hutami Nainggolan; Eliza '; Shorea Khaswarina (Program Studi Pendidikan Ekonomi Universitas Riau, 2016)
The purpose of this study was 1). to distribution consumption the expenses of food and non-food household rubber farmers Ex UPP TCSDP and independent smallholder. 2) to compare the expenses of food and non-food household rubber farmers Ex UPP TCSDP and independent smallholder This research was done in Bina Baru Village Kampar Kiri Tengah District in Kampar Regency. Survey method was used in order to get the data through disproportional random sampling to 30 Ex UPP TCSDP rubber farmers and 30 smallholder rubbers. This research used the distribution of consumption expenditure of food and non-food analysis and a comparative analysis (test t). As the results showed that the average expenditure of independent smallholder rubber is Rp. 2,563,020 bigger than rubber farmer Ex UPP TCSDP which expends of Rp. 1,889,957 in a month. Seen from the consumption patterns, non-food consumption of the rubber farmers Ex UPP TCSDP and independent smallholder is greater than food consumption. Based on t-test 95% confidence level, t-count gets 1.920 while t-table gets 1.520. It indicates that t-count is greater than t-table. So, it can be concluded immediately null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted, so the expenditure between rubber farmers Ex UPP TCSDP and independent smallholders are differences in real.